First Observations of E-Region Near Range Echoes Partially Modulated by F-Region Traveling Ionospheric Disturbances Observed by the Same SuperDARN HF Radar - Kosch, Michael J.; Hiyadutuje, Alicreance; Stephenson, Judy A. E. (Journal of Geophysical Research: Space Physics, 2022)
We present the first observations from SuperDARN HF radar data of E-region Near Range Echoes (NREs) whose amplitudes are partially modulated by Medium-Scale Traveling Ionospheric Disturbances (MSTIDs) propagating in the F-region overhead that have been observed by the same radar in the far ranges. SuperDARN NREs occur normally ∼180–315 km downrange from the radar at ∼95–125 km altitude. Selected observations of TID-modulated NREs are presented from SANAE and Zhongshan Antarctic SuperDARN radars for both summer and winter seasons as well as geomagnetic active and quiet times. We show that the most likely mechanism is partial modulation of the Gradient Drift Instability (GDI), which is responsible for producing the NREs. GDI is driven by the velocity difference between neutrals and ions and may appear in the E-region ionosphere wherever suitable plasma density gradients exist. GDI already present in the E-region can be partially modulated by an MSTID passing overhead in the F-region via the additional MSTID polarization electric field mapped down in altitude along the equipotential magnetic field lines, thereby partially modulating the NRE amplitudes as observed.